TENAGA KERJA WANITA DALAM PERSPEKTIF GENDER DI NUSA TENGGARA BARAT - Yusrini, Bq. Ari (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
Gender is a concept that refers to a system of roles and relationships between women and men that are not determined by biological differences, but are determined by the social, political, and economic environment. In the preparation of this article, the author uses literature study method. Library study is used to extract information related to writing. The result of the research shows that in general the reason for being TKW; earning a great income, seeking work experience, finding a life partner, and becoming a foreign citizen. Another result indicates that the poverty factor is the main driving factor for women to become TKW as an effort to overcome the burden of family social economic burden. Social status in rural communities tends to be measured in terms of material, such as residence, vehicle, land area and other things.